Racial depictions in visual culture during World War One: A transnational and comparative study - Kofoed Hansen, Christian; Simonsen, Gustav (Culture and History: Student Research Papers, 2023)
How can we understand British depictions of the German ‘race’, if they are understood as belonging to the same racial category? We argue that an analysis of racial depictions must be based on historical and cultural understandings. We present ‘race’ as an all-encompassing, flexible historical phenomenon, that includes cultural racism. We found that cultural and biological racism overlapped, working in tandem to create a single depiction within a spectrum of culturally or biologically based racial stereotypes. We argue that racialized stereotypes were deployed in both intra-white and non-white depictions depending on the desired function of the propaganda resulting in both positive or/and negative portrayals that worked mainly in consolidating the Self and Othering the enemy – with the exception of white depictions of non-white soldiers often showcasing Othering exotic elements.